Orzubek USING TPR (TOTAL PHYSICAL RESPONSE) TEACHING METHOD AT CLASS: USING TPR (TOTAL PHYSICAL RESPONSE) TEACHING METHOD AT CLASS - Anarbaev, Orzubek (Журнал иностранных языков и лингвистики, 2022)
In recent years the question of foreign language teaching has received a closer attention in Uzbekistan. It is evidenced by the adoption of the National Programme for Personnel Training and a number of subsequent documents that have created favorable conditions for the development of methods in language teaching. Resolution “On measures for further improvement of the study of foreign languages” has been adopted recently.